CEO birth order and corporate social responsibility behaviors: The moderating effect of female sibling and age gap - Zheng, Minna; Ren, Guangqian; Wu, Sihong; Jiang, Zezhen (Frontiers in Psychology, 2022)
Corporate social responsibility (CSR) is one of the most important business strategies which helps enterprises obtain competitive advantage and improve performance. Scholars have conducted many beneficial studies on the driving factors of CSR behaviors from the perspective of CEO traits, but rarely focus on the impact of the CEO's early family experiences. This study aims to fill this research gap by investigating the influence of CEO birth order on firms' CSR behaviors, and further exploring the possible moderating effects of the presence of a female sibling and the age gap between the CEO and the closest sibling. This study takes Chinese non-financial private listed companies from 2010 to 2017 as the research samples, and empirically tests the relationship between CEO birth order and a firm's CSR behaviors. The empirical results show that CEO birth order negatively influences corporate social responsibility behaviors, and this relationship would be weakened when the CEO has a female sibling or the age gap between CEO and the closest sibling is larger. This paper extends the research on personal family factors from the field of social psychology to the business field and finds a new driving factor of corporate social responsibility behavior from the perspective of the CEOs' early family factors.